Avaliação do efeito do pré e pós-condicionamento em modelo de isquemia renal transitória: estudo comparativo experimental em ratos - Arantes, Vinicius Monteiro [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Background: Ischemia-reperfusion injury (IRI) is an unavoidable aspect of transplantation, as well as an important cause of acute kidney injury in clinical practice. Restoration of the blood supply after an ischemic period activates an inflammatory cascade associated with multiple processes, including ion accumulation, free reactive oxygen species (ROS) formation, endothelial dysfunction, and immune activation. Ischemic “conditioning” refers to the application of a brief series of ischemic periods followed by reperfusion in the setting of major ischemia. In ischemic preconditioning (IPC), the conditioning stimulus is applied before the major ischemic event, whereas in ischemic postconditioning (IPoC), it is applied after the event. Methods: Forty Wistar rats were randomized into five groups: Sham (S): laparotomy; Control (C): laparotomy and 30 min ischemia; Preconditioning (PRE): laparotomy, IPC, and 30 min ischemia; Preconditioning and Postconditioning (PRE/POST): laparotomy, IPC, 30 min ischemia, and IPoC; Postconditioning (POST): laparotomy, 30 min ischemia, and IPoC. Serum analyses of creatinine and neutrophil gelatinaseassociated lipocalin (NGAL) were performed, and renal histology was also examined. Results: Severe tubular injury and increases in creatinine were observed in all groups except the S group, and no significant differences were detected between the other groups (S<C=PRE=PRE/POST=POST). Conclusions: IPC and IPoC, together or separately, were unable to exert a protective effect against tubular cell injury and preserve kidney function. The duration of the ischemic period is a critical aspect of the conditioning strategy. Our results indicate that conditioning may not improve the outcome, and it may even be harmful.

Introdução: a lesão por isquemia-reperfusão (LIR) é uma importante causa de lesão renal aguda experimentada na prática clínica. A restauração da perfusão aos tecidos após um período de isquemia inicia uma cascata de inflamação associada ao acúmulo de íons, formação de espécies reativas de oxigênio (ERO), disfunção endotelial e ativação imune. O condicionamento isquêmico é a aplicação de breves ciclos de interrupção seguidas de restauração do fluxo sanguíneo, tendo o objetivo de adaptar os tecidos à isquemia. Pode ser aplicado antes do estímulo principal, como précondicionamento (PCI), ou depois, sendo denominado pós-condicionamento (PCoI). Metodologia: estudo experimental realizado com 40 ratos wistar, divididos em cinco grupos para análise comparativa: Sham (S): laparotomia; Controle (C): laparotomia e 30 min de isquemia; Pré-condicionamento (PRE): laparotomia, PCI e 30 min de isquemia; Pré e Pós-condicionamento (PRE/POS): laparotomia, PCI, 30 min de isquemia e PCoI; Pós-condicionamento (POS): laparotomia, 30 min de isquemia e PCoI. A comparação entre os grupos foi realizada pela análise bioquímica sérica de creatinina, ureia, lipocalina associada à gelatinase de neutrófilos (NGAL) e histolologia. Resultados: apenas o grupo Sham apresentou valores estatisticamente menores dos marcadores de lesão renal e menor incidência de lesão tubular renal à histologia (S<C=PRÉ=PRÉ/PÓS=PÓS). Discussão e conclusão: no presente estudo, o PCI e o PoCI, isoladamente ou em conjunto, foram incapazes de prevenir dano estrutural tubular renal. A duração do período isquêmico é um aspecto crítico nas estratégias de condicionamento. Os resultados encontrados indicam que o condicionamento pode não melhorar os desfechos, e em alguns casos pode ser prejudicial.
Effects of ischemic preconditioning and postconditioning in an ischemia-reperfusion model: a comparative experimental study in rats
Keywords: Ischemic preconditioning; Ischemic postconditioning; Kidney; Rats; Acute kidney injury; Pré-condicionamento isquêmico; Pós-condicionamento isquêmico; Rim; Ratos; Lesão renal aguda